Monitoring of the Deposition of PAHs and Metals Produced by a Steel Plant in Taranto (Italy) - M. Amodio; G. de Gennaro; A. Di Gilio; M. Tutino (Advances in Meteorology)
A high time-resolved monitoring campaign of bulk deposition of PAHs and metals was conducted near the industrial area and at an urban background site in province of Taranto (Italy) in order to evaluate the impact of the biggest European steel plant. The deposition fluxes of the sum of detected PAHs at the industrial area ranged from 92 to 2432 ng m−2d−1. In particular the deposition fluxes of BaP, BaA, and BkF were, on average, 10, 14, and 8 times higher than those detected at the urban background site, respectively. The same finding was for metals. The deposition fluxes of Ni (19.8 µg m−2 d−1) and As (2.2 µg m−2 d−1) at the industrial site were about 5 times higher than those at the urban background site, while the deposition fluxes of Fe (57 mg m−2d−1) and Mn (1.02 mg m−2d−1) about 31 times higher. Precipitation and wind speed played an important role in PAH deposition fluxes. Fe and Mn fluxes at the industrial site resulted high when wind direction favored the transport of air masses from the steel plant to the receptor site. The impact of the industrial area was also confirmed by IP/(IP + BgP), IP/BgP, and BaP/BgP diagnostic ratios.